1991
DOI: 10.1192/bjp.158.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Divergent Aetiological Factors in Obsessive-Compulsive Disorder

Abstract: Among 307 adults with OCD, early onset (age 5-15 years) was more common in men and later onset (age 26-35 years) in women. Early onset was associated with more checking, and late onset with more washing. More women than men had a history of treated depression; 12% of the women but none of the men had a history of anorexia. More women than men were married. Gender-divergent features may reflect differential aetiological factors. Our sample resembled others in the literature in its slight overall female preponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
2
15

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 33 publications
12
71
2
15
Order By: Relevance
“…29 An Italian study found a higher frequency of insidious onset and chronic course among male sufferers and more episodic course among females. 19 According to Noshirvani et al, 17 similarly to schizophrenia, OCD cases with an early onset are usually more severe, reflecting the influence of cerebral lesions or constitutional aspects to which men are more vulnerable than women. Likewise, Bogetto et al 19 consider that early OCD onset is not strongly related to the impact of stressful life events but, conversely, could indicate a higher influence of biological lesions to which men are more predisposed.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
“…29 An Italian study found a higher frequency of insidious onset and chronic course among male sufferers and more episodic course among females. 19 According to Noshirvani et al, 17 similarly to schizophrenia, OCD cases with an early onset are usually more severe, reflecting the influence of cerebral lesions or constitutional aspects to which men are more vulnerable than women. Likewise, Bogetto et al 19 consider that early OCD onset is not strongly related to the impact of stressful life events but, conversely, could indicate a higher influence of biological lesions to which men are more predisposed.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
“…Çocukluk çağında erkeklerde daha fazla görülürken, erişkin dönemde kadın erkek oranının yaklaşık olarak aynı olduğu ya da kadınlarda daha fazla görüldüğü bildirilmiştir 7,8 . Yazında kadınlarda en sık eşlik eden psikiyatrik eştanılar majör depresyon, yeme bozuklukları, dürtü kontrol bozuklukları iken, erkeklerde sosyal fobi, tik bozuklukları, madde kullanım bozukluklarıydı 9,11,[13][14][15][16][17]19 . Yaptığımız araştırmada ise cinsiyetler arasında psikiyatrik eştanı açısından istatistiksel olarak anlamlı bir farklılık bulunamamıştır.…”
Section: İlk Olarak Esquirol Tarafından Tanımlananunclassified
“…Os estudos sistematizados têm demonstrado que pelo menos 50% dos pacientes com TOC apresentam um outro transtorno do eixo I, 4,5,[10][11][12][13][14][15][16][17] e no mínimo 40% preenchem critérios para um transtorno de personalidade. A presença de comorbidade parece conferir estabilidade e melhorar a validade diagnóstica.…”
Section: Aspectos Epidemiológicos Da Comorbidade Em Tocunclassified